Bioactivity mapping of secondary metabolite compounds of Pandanus amaryllifolius leaves as anti-inflammatory using in silico - Arrohmah, Robiatus Sholichah; Ibtisam, Afina Anjani; Sa’adah, Siti Malihatus; Putri, Fensy Rania; Fitriyah, Fitriyah (Journal of Natural Sciences and Mathematics Research, 2023)
Inflammation is one of the primary responses of the immune system to infection and irritation. Anti-inflammatory drugs generally cause side effects. Anti-inflammatory developed by reducing side effects use many natural materials such as plants. The parts of the plant used include fruits, leaves, stem bark, rhizomes, and flowers. One of the plants that can be used as an anti-inflammatory is Pandanus amaryllifolius. P. amaryllifolius leaves contain several materials, such as flavonoids, alkaloids, saponins, tannins, polyphenols, and dyes. This study aimed to determine the anti-inflammatory potential of the secondary metabolites of Pandanus amaryllifolius leaves using the in silico method. The research used a descriptive exploratory method and was conducted from December 2022 – January 2023. In silico mapping of the bioactivity of active compounds was carried out using several software or websites: knapsack database (www.knapsackfamily.com), NCBI PubChem database (https://pubchem.ncbi.nlm.nih.gov/), PASS Online Way 2 Drug (http://www.way2drug.com/passonline/) and ADME Swiss Analysis (http://www.swissadme.ch/). The result shows P. amarylifolius has 31 active compounds. The compounds were then analyzed using Pass Online with 18 anti-inflammatory parameters. It explained that 3 compounds met the rules for Pa values > 0.7, namely compounds 6E-Pandanamine (0.758), Pandamenyamine (0.735), and Pandamarilactone 1 (0.709). The results of pharmacokinetic tests using Lipinski